New species of Eleutherodactylus (Amphibia: Leptodactylidae) from Guaraquecaba, Atlantic Forest of Brazil - Castanho, Luciano Mendes [UNESP]; Haddad, Célio F. B. [UNESP] (My University, 2000)
A new species of the leptodactylid frog genus Eleutherodactylus is described from Guaraquecaba, State of Parana, southern Brazil. The new species is characterized by its large size, slightly rugose to rugose dorsal skin texture, robust body, and low number of pulses per call. Descriptions of the advertisement calls of the new species and of E. manezinho, a close related species, are provided, as well as information on natural history.
Keywords: Eleutherodactylus; Eleutherodactylus manezinho